3x-(x-1)=7

Simple and best practice solution for 3x-(x-1)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(x-1)=7 equation:


Simplifying
3x + -1(x + -1) = 7

Reorder the terms:
3x + -1(-1 + x) = 7
3x + (-1 * -1 + x * -1) = 7
3x + (1 + -1x) = 7

Reorder the terms:
1 + 3x + -1x = 7

Combine like terms: 3x + -1x = 2x
1 + 2x = 7

Solving
1 + 2x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 2x = 7 + -1

Combine like terms: 1 + -1 = 0
0 + 2x = 7 + -1
2x = 7 + -1

Combine like terms: 7 + -1 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| 14/70=p/100 | | 5m-11=4m+5 | | x^3-3x^2+15x-25=0 | | 6d=-6+5d | | v-4=16 | | 4-3b=5 | | 10/20=80%/100 | | (6x+9)+7y=6x+(9+7y) | | -4=-20/3+b | | 5-1/5g=12 | | 5+2j=2j+6 | | C=7/3(k-64) | | -2k=-10-3k | | 3x^2-90x-10=0 | | -10=5(2w+-4) | | 90x^2-90x-10=0 | | 9+2(5y+3)=135 | | 2(3x-2)+14=133 | | 2/3x+6=x+1/4x | | -(3-9y)= | | 2(x+6)=2(-x+6.5) | | 4(-8p+5)=-32p-26 | | 2n+1.5n=10.5 | | -10-6g=-8g+10 | | 3x^2-2=190 | | -4a=14a-12(4a+10) | | 3/5=x/100 | | Y=x^3+2x^2-x+3 | | 48=7m+m | | -3(2u+5)+3.5=-1u | | .13x+.03(50000-x)=6000 | | 3m+9x=24 |

Equations solver categories